HEAL Africa score to predict failure of surgical repair of obstetric urethro-vaginal fistula in the Democratic Republic of the Congo - Justin Lussy Paluku; Susan A. Bartels; Jonathan ML. Kasereka; Barthelemy Kasi Aksanti; Eugénie Mukekulu Kamabu; Olivier Mukuku; Zacharie Kibendelwa Tsongo; Stanis Okitotsho Wembonyama; Charles Wembonyama Mpoy; Jeannot Sihalikyolo Juakali (BMC, 2024)
Abstract Introduction Obstetric fistula (OF) repair surgery aims to restore the anatomical and functional integrity of the urinary tract, allowing affected women to regain their dignity and quality of life. However, in some cases, this surgical repair may fail. The objective of this study was to develop a predictive score to identify factors associated with the failure of surgical repair of obstetric urethro-vaginal fistula (FSROUVF) in the Democratic Republic of the Congo (DRC). Methods This is an analytical cross-sectional study of 358 patients with obstetric urethro-vaginal fistula (OUVF) who received surgical repair. We conducted bivariate and multivariate analyses. Score discrimination was assessed using the receiver operating characteristic (ROC) curve, C-index, and score calibration according to the Hosmer-Lemeshow test. Results Surgical repair of OUVF failed in 24.86% of cases (89/358). After logistic modelling, 6 criteria predicted FSROUVF: the use of intravaginal indigenous products (AOR = 3.59; 95% CI: 1.51-8.53), the presence of fibrosis (AOR = 6.37; 95% CI: 1.70-23.82), the presence of 2 or more fistulas in the same patient (AOR = 7.03; 95% CI: 3.14-15.72), the total urethral damage (AOR = 3.29; 95% CI: 1.36-7.95), the fistula size > 3 cm (AOR = 5.65; 95% CI: 2.12-15.01), and the postoperative infection (AOR = 351.10; 95% CI: 51.15-2409.81). A score of 0 to 14 was obtained, with a value ≤5 points indicating a low risk of FSROUVF, a value between 6 and 8 indicating a moderate risk, and a value ≥9 points corresponding to a high risk of FSROUVF. The area under the ROC curve of the score is 0.938 with a sensitivity of 60.67%, a specificity of 96.28%, a positive predictive value of 84.38%, and a negative predictive value of 88.10%. Conclusion We report a FSROUVF rate in the DRC approaching a quarter of operative patients. Predictors of failure included fibrosis, presence of 2 or more fistulas, total urethral involvement, fistula size greater than 3 cm, postoperative infection, and use of intravaginal indigenous products. These factors are constitutive of the HEAL Africa score, which once validated, may have value in pre-operative counselling of patients. This study could be valuable for policy and strategies to address the problem of OUVF in the DRC and in resource limited settings more generally.